Preparation method and application of lithium ion battery silicon-based negative electrode material based on metal fluoride additive
By introducing metal fluoride and carbon coating on the surface of the silicon anode, the problems of volume expansion, solid electrolyte membrane breakage and poor conductivity of the silicon anode during cycling are solved, significantly improving the electrochemical performance and stability of lithium-ion batteries.
Patent Information
- Application Number
- CN202411748924.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The volume expansion/contraction of the silicon negative electrode during the cycle leads to increased stress, crushing and powdering, affecting electrical contact and capacity attenuation; the solid electrolyte membrane is constantly broken and recombined, resulting in the consumption of electrolyte and lithium ions; the conductivity of silicon is poor, Limit the diffusion rate of lithium ions.
Metal fluoride is introduced on the surface of micron silicon to build an interface with fast lithium ion transmission and good mechanical properties. The conductivity is improved through carbon coating and the volume expansion of silicon is suppressed.
The interface reaction dynamics of lithium ion battery silicon -based pole material is improved, the interface stability is enhanced, the volume expansion is suppressed, and the transmission rate and electrochemical performance of lithium ions are improved.
Smart Images

Figure CN119361611A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of a silicon-based negative electrode of a lithium ion battery and application thereof. Background Art
[0002] At present, the widely used graphite negative electrode materials have low specific capacity, and the capacity in the battery is close to the theoretical limit, which cannot meet the needs of higher performance lithium-ion batteries. Therefore, the development of new negative electrode materials with high specific capacity, high energy density and high safety is crucial for the future application of lithium-ion batteries. Silicon (Si) materials as negative electrodes of lithium-ion batteries have the following advantages: high theoretical specific capacity (4200mAh g -1 , Li 22 Si5), which is more than 10 times that of traditional graphite materials; low operating voltage, which will further improve the energy density of the battery when matched with high-capacity and high-voltage NCM positive electrodes; abundant reserves and wide sources, it is the second most abundant element in the earth's crust, with a content of 26.3%, second only to oxygen; it is non-toxic and environmentally friendly. Therefore, silicon (Si) negative electrode is recognized by the industry as one of the first choices for developing the next generation of high-energy density lithium-ion battery negative electrode materials. However, compared with traditional commercial graphite negative electrodes, silicon faces the problem of huge volume expansion. Several challenges of silicon anodes limit their further application: (1) Silicon anodes will undergo large volume expansion / contraction during the cycle, which will generate huge stress, causing silicon to break and pulverize, and ultimately lose electrical contact and cause rapid capacity decay; (2) The solid electrolyte membrane (SEI) of the silicon anode will continue to break and reorganize during the cycle, and this process will be repeated, causing the SEI to become thicker and accompanied by a large consumption of electrolyte and lithium ions; (3) In terms of the properties of the material itself, silicon is a common intrinsic semiconductor material with poor conductivity, which greatly limits the diffusion rate of lithium ions in the silicon anode, seriously affecting the practical application of the silicon anode. Summary of the invention
[0003] The present invention aims to solve the technical problems of poor lithium ion transmission between the silicon and electrolyte interface of the existing silicon negative electrode and poor mechanical properties of SEI, and provides a preparation method and application of lithium ion battery silicon-based negative electrode materials based on metal fluoride additives. The present invention introduces a metal fluoride into micron silicon, constructs a layer of fast ion transmission and good mechanical performance interface on the silicon surface, and finally further improves the conductivity of the material through carbon coating while suppressing the volume expansion of silicon, solves the problems of poor lithium ion transmission between the silicon and electrolyte interface and poor mechanical properties of SEI, further improves the reaction kinetics of the silicon negative electrode interface, suppresses the volume effect and stabilizes the interface.
[0004] The method for preparing the silicon-based negative electrode material for lithium-ion batteries based on metal fluoride additives of the present invention is carried out according to the following steps:
[0005] 1. Dissolve the metal fluoride in a solvent, then add silicon particles and stir for 3 to 4 hours to obtain a mixed solution A;
[0006] 2. Add the resin to the mixed solution A and stir for 3 to 5 hours to obtain the mixed solution B;
[0007] 3. heating the mixed solution B obtained in step 2 in an oil bath to evaporate the solvent to obtain a solid mixture;
[0008] Fourth, the solid mixture obtained in step 3 is placed in a tube furnace, heated to 800-900°C in an argon atmosphere and calcined for 2-3 hours to obtain a lithium-ion battery silicon-based negative electrode material based on a metal fluoride additive, denoted as Si-M x F y @C.
[0009] Furthermore, the metal fluoride in step 1 is one or a combination of MgF2, CaF2, ZnF2 and SnF2.
[0010] Furthermore, the particle size of the silicon particles described in step 1 is 1 to 3 μm.
[0011] Furthermore, the solvent in step 1 is one or more of methanol, ethanol and propanol.
[0012] Furthermore, the mass ratio of silicon to metal fluoride in step 1 is 1:(6-8).
[0013] Furthermore, the resin in step 2 is one or more of polyacrylonitrile, polyvinyl pyrrolidone, and phenolic resin;
[0014] Furthermore, the evaporation temperature in step three is 60°C to 80°C.
[0015] The application of the lithium-ion battery silicon-based negative electrode material based on metal fluoride additives prepared by the above method is to be used in lithium-ion batteries.
[0016] The present invention uses metal fluoride as an additive, dissolves it in a solvent, and then mixes it with silicon to coat the surface of micron silicon with metal fluoride. During the first cycle, the metal fluoride can form a fast lithium ion conductor LiF / electron conductor Li x M mixed interface layer, and has high mechanical toughness, enhances the interface stability of silicon, and finally forms a carbon layer through polymer pyrolysis, further improves the reaction kinetics, inhibits the volume effect and stabilizes the interface, and obtains a silicon negative electrode with greatly improved performance. The lithium ion battery silicon-based negative electrode material prepared by the present invention is cyclic at a current of 0.2C and a voltage range of 0.01V to 3V. After 200 cycles, the remaining capacity is 1300 to 1450 mAh g-1 .
[0017] The present invention uses metal fluorides to modify micron silicon, effectively improves the interface reaction kinetics, increases the mechanical strength of the interface SEI layer, enhances the interface stability, effectively inhibits the volume expansion of micron silicon particles, solves the problems of poor lithium ion transmission between the silicon and electrolyte interface and poor SEI mechanical properties, and has a simple process and is easy to implement on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is an elemental analysis diagram of the lithium-ion battery silicon-based negative electrode material prepared in Example 1;
[0019] Figure 2 is a scanning electron microscope photograph of the lithium-ion battery silicon-based negative electrode material prepared in Example 1;
[0020] Figure 3 This is a high-magnification scanning electron microscope photograph of the lithium-ion battery silicon-based negative electrode material prepared in Example 1;
[0021] Figure 4 This is the XPS spectrum of the lithium-ion battery silicon-based negative electrode material prepared in Example 1;
[0022] Figure 5 is a GITT curve of the lithium-ion battery silicon-based negative electrode material prepared in Example 1;
[0023] Figure 6 is a cycle performance curve diagram of the lithium-ion battery silicon-based negative electrode material prepared in Example 1;
[0024] Figure 7 1 is a graph showing the cycle performance of lithium-ion battery silicon-based negative electrode materials prepared in Example 1, Comparative Example 1 and Comparative Example 2;
[0025] Figure 8 This is a cycle performance curve of the lithium-ion battery silicon-based negative electrode material prepared in Example 2. DETAILED DESCRIPTION
[0026] The beneficial effects of the present invention are verified by the following examples.
[0027] Example 1: The preparation method of the silicon-based negative electrode material for lithium-ion batteries based on metal fluoride additives of this example is carried out according to the following steps:
[0028] 1. Add 0.05 g of SnF2 to 15 mL of ethanol, then add 0.35 g of silicon particles with an average particle size of 3 μm, and stir for 3 h to obtain a mixed solution A;
[0029] 2. Add 0.04 g of polyacrylonitrile resin to mixed solution A and stir for 3 h to obtain mixed solution B;
[0030] 3. heating the mixed solution B obtained in step 2 in an oil bath at 80° C. to evaporate the solvent and obtain a solid mixture;
[0031] 4. The solid mixture obtained in step 3 is placed in a tubular furnace, heated to 850° C. under an argon atmosphere and calcined for 2 h to obtain a lithium-ion battery silicon-based negative electrode material based on a metal fluoride additive, denoted as Si-SnF2@C.
[0032] The scanning electron microscope image of the silicon-based negative electrode material for lithium-ion batteries obtained in this embodiment is as follows Figure 1 As shown, from Figure 1 It can be seen that the metal fluoride SnF2 is coated on the surface of the silicon particles without changing the morphology of the silicon particles.
[0033] The high-magnification scanning electron microscope image of the silicon-based negative electrode material for lithium-ion batteries obtained in this embodiment is as follows: Figure 2 As shown, from Figure 2 It can be seen that there is a certain agglomeration phenomenon of silicon particles.
[0034] The elemental analysis diagram (Mapping) of the lithium-ion battery silicon-based negative electrode material obtained in this embodiment is as follows Figure 3 As shown, from Figure 3 It can be seen that SnF2 is dispersed on the silicon surface.
[0035] The XPS test graph of the silicon-based negative electrode material for lithium-ion batteries obtained in this embodiment is as follows Figure 4 As shown, from Figure 4 It can be seen that the metal fluoride on the surface of the prepared silicon negative electrode did not undergo a change in valence state, indicating its stable existence.
[0036] The lithium ion battery silicon-based negative electrode material prepared in Example 1 and the silicon particles in step 1 were subjected to a constant current intermittent titration test. By controlling the pulse current and relaxation time, the GITT curve of the lithium ion battery silicon-based negative electrode material and the original silicon particles was obtained as shown in FIG. Figure 5 As shown, from Figure 5 It can be seen that the introduction of metal fluoride significantly increases the ion transport rate, indicating that it improves the interfacial kinetic reaction of silicon.
[0037] The lithium-ion battery silicon-based negative electrode material prepared in Example 1 and the silicon particles in step 1 were used as negative electrode materials to prepare electrodes. The negative electrode material: conductive carbon black: binder were prepared into a slurry at a ratio of 8:1:1, and then coated on a copper foil, dried at 60°C for 6h, and then cut into 12mm negative electrode sheets. Half cells were assembled and tested at a current of 0.2C (1C = 4200mAh g -1 ), the voltage range is 0.01V~3V, and the activation current is 0.01C for cycle performance test. The cycle performance curve is shown in the figure below. Figure 6 As shown, from Figure 6 It can be seen that the introduction of metal fluoride improves the interface stability of the silicon negative electrode and inhibits the volume effect, thereby improving the electrochemical performance of the silicon negative electrode. The capacity of the modified silicon negative electrode is still 1446.6 mAh g after 200 cycles at 0.2C. -1 Compared with the original silicon negative electrode, its cycle performance has been greatly improved.
[0038] Comparative Example 1: This comparative example differs from Example 1 in that the operation in step 1 is replaced by:
[0039] 1. Add 0.05 g of SnF2 to 15 mL of ethanol, then add 0.45 g of silicon particles with an average particle size of 3 μm, and stir for 3 h to obtain a mixed solution A; the other steps and parameters are the same as in Example 1.
[0040] Comparative Example 2: This comparative example differs from Example 1 in that the operation in step 1 is replaced by:
[0041] 1. Add 0.05 g of SnF2 to 15 mL of ethanol, then add 0.25 g of silicon particles with an average particle size of 3 μm, and stir for 3 h to obtain a mixed solution A; the other steps and parameters are the same as in Example 1.
[0042] Compared with Example 1, Comparative Example 1 and Comparative Example 2, the ratio of silicon to metal fluoride is different. In Example 1, the mass ratio of SnF2 to silicon particles is 1:7, in Comparative Example 1, the mass ratio of SnF2 to silicon particles is 1:9, and in Comparative Example 2, the mass ratio of SnF2 to silicon particles is 1:5. The lithium-ion battery silicon-based negative electrode material prepared in Example 1, Comparative Examples 1 and 2 is prepared into an electrode, wherein the negative electrode material: conductive carbon black: binder is prepared into a slurry in a ratio of 8:1:1, and then coated on a copper foil, dried at 60°C for 6h, and then cut into 12mm negative electrode sheets, assembled into half cells, and at a current of 0.2C (1C=4200mAh g -1 ), the voltage range is 0.01V~3V, and the activation current is 0.01C for cycle performance test. The cycle performance curve is shown in the figure below. Figure 7 As shown. Figure 7 It can be seen that the capacity of the negative electrode material prepared in comparative example 1 is only 803.6 mAh g after 200 cycles. -1 The capacity of the negative electrode material prepared in comparative example 2 was only 165.6 mAh g after 200 cycles. -1 By comparing the materials obtained in Example 1 with those obtained in Comparative Examples 1 and 2, it is shown that a good technical effect can be achieved when the mass ratio of metal fluoride to silicon is 1:7.
[0043] Example 2: The preparation method of the silicon-based negative electrode material for lithium-ion batteries based on metal fluoride additives of this example is carried out according to the following steps:
[0044] 1. Add 0.05 g of MgF2 to 15 mL of ethanol, then add 0.35 g of silicon particles with an average particle size of 3 μm, and stir for 3 h to obtain a mixed solution A;
[0045] 2. Add 0.04 g of phenolic resin to mixed solution A and stir for 3 h to obtain mixed solution B;
[0046] 3. heating the mixed solution B obtained in step 2 in an oil bath at 80° C. to evaporate the solvent and obtain a solid mixture;
[0047] 4. The solid mixture obtained in step 3 is placed in a tubular furnace, heated to 850° C. in an argon atmosphere and calcined for 2 h to obtain a lithium-ion battery silicon-based negative electrode material based on a metal fluoride additive, which is denoted as Si-MgF2@C.
[0048] The lithium-ion battery silicon-based negative electrode material prepared in Example 2 was prepared into an electrode. The specific method was to prepare a slurry of negative electrode material: conductive carbon black: binder in a ratio of 8:1:1, then apply it on a copper foil, dry it at 60°C for 6h, and then cut it into 12mm negative electrode sheets. Half-cells were assembled and tested at a current of 0.2C (1C = 4200mAh g -1 ), the voltage range is 0.01V~3V, and the activation current is 0.01C for cycle performance test. The cycle performance curve is shown in the figure below. Figure 8 As shown. Figure 8 It can be seen that the use of MgF2 to prepare lithium-ion battery silicon-based negative electrode materials has a remaining capacity of 1327.04 mAh g after 200 cycles. -1 .
Claims
1. A method for preparing a lithium-ion battery silicon-based negative electrode material based on a metal fluoride additive, characterized in that: The method proceeds as follows:
1. Dissolve the metal fluoride in a solvent, then add silicon particles and stir for 3 to 4 hours to obtain a mixed solution A; 2. Add the resin to the mixed solution A and stir for 3 to 5 hours to obtain the mixed solution B; 3. heating the mixed solution B obtained in step 2 in an oil bath to evaporate the solvent to obtain a solid mixture; Fourth, the solid mixture obtained in step 3 is placed in a tube furnace, heated to 800-900°C in an argon atmosphere and calcined for 2-3 hours to obtain a lithium-ion battery silicon-based negative electrode material based on a metal fluoride additive, denoted as Si-M x F y @C.
2. The method for preparing a lithium-ion battery silicon-based negative electrode material based on a metal fluoride additive according to claim 1, characterized in that: The metal fluoride described in step 1 is one or a combination of MgF2, CaF2, ZnF2 and SnF2.
3. The method for preparing a lithium-ion battery silicon-based negative electrode material based on a metal fluoride additive according to claim 1 or 2, characterized in that: The particle size of the silicon particles described in step 1 is 1 to 3 μm.
4. The method for preparing a lithium-ion battery silicon-based negative electrode material based on a metal fluoride additive according to claim 1 or 2, characterized in that: The solvent described in step 1 is one or more of methanol, ethanol and propanol.
5. The method for preparing a lithium-ion battery silicon-based negative electrode material based on a metal fluoride additive according to claim 1 or 2, characterized in that: The mass ratio of silicon to metal fluoride in step 1 is 1:(6-8).
6. The method for preparing a lithium-ion battery silicon-based negative electrode material based on a metal fluoride additive according to claim 1 or 2, characterized in that: The resin described in step 2 is one or more of polyacrylonitrile, polyvinyl pyrrolidone and phenolic resin.
7. The method for preparing a lithium-ion battery silicon-based negative electrode material based on a metal fluoride additive according to claim 1 or 2, characterized in that: The evaporation temperature described in step 3 is 60°C to 80°C.
8. Application of lithium-ion battery silicon-based negative electrode material based on metal fluoride additive prepared by the method of claim 1, characterized in that The application is to use lithium-ion battery silicon-based negative electrode materials based on metal fluoride additives in lithium-ion batteries.
Citation Information
Patent Citations
High-capacity silicon-based anode material for lithium ion battery and preparation method thereof, and lithium ion battery
CN105576209A
Silicon-based negative electrode material of lithium ion battery and preparation method thereof
CN109950515A
Carbon-coated metal fluoride modified silicon negative electrode material and preparation method and application thereof
CN116544397A
Cited By
Silicon-based lithium ion battery negative electrode slurry as well as preparation method and application thereof
CN122025561A
Silicon-based negative electrode sheet and construction method and application thereof using ammonium phosphate salt additive
CN122739260A